Future financial behavior and financial literacy of young muslim generations - Khusna, Atiatul; Sanjaya, Intan Winda Widya; Rohmah, Siti; Saifudin, Saifudin (Islamic Accounting Journal, 2024)
Objective & object: Financial literacy can provide an understanding of humans related to financial behavior in everyday life, such as saving, how to spend money, how to take credit, making investment decisions, and how humans manage their finances. This quantitative research aims to determine the influence of financial knowledge, financial skills, and financial efficacy on financial behavior in people in Central Java. Methods: The sample of this study was PTKIN students in Central Java, selected by incidental sampling technique. Multiple linear regression analysis tools were used with the help of SPSS software. Results & Conclusions: The study's results proved that financial knowledge, financial self-efficacy, and financial skills positively and significantly affect financial behavior. Limitations: This research uses questionnaires as data collection, the target respondents are PTKIN students in Central Java. Not all respondents come from the faculty of economics and Islamic business, so their knowledge of financial literacy depends on their individual understanding. Implications: This research can be used as a reference for the government to improve financial literacy in the younger generation so that they can welcome the Golden Indonesia in 2045. This research also strengthens accounting theory in the field of science related to financial behavior.